Creating a sustainable economy within environmental limits - Asquith, Mike; Marinakis, Pantelis (Ökologisches Wirtschaften - Fachzeitschrift, 2022)
The European Green Deal’s focus on decoupling economic growth from environmental pressures is essential. But Europe can also increase its resilience by reducing its dependence on economic growth. Governments have a vital role in enabling this change.